Wireless mobile ad-hoc sensor networks for very large scale cattle monitoring - Radenkovic, Milena; Wietrzyk, Bartosz (2006)
This paper investigates the use of wireless mobile ad hoc sensor networks in the nationwide cattle monitoring systems. This problem is essential for monitoring general animal health and detecting outbreaks of animal diseases that can be a serious threat for the national cattle industry and human health.